Selective octopaminergic tuning of mushroom body circuits during memory formation - Ulrike S. Franke; Alexandra Großjohann; Samantha Aurich; Ines Köhler; Marius Lamberty; Sara Granato; Alice Fallaha; Jana Breitfeld; Peter Kovacs; Mareike Selcho; Robert J. Kittel; Andreas S. Thum; et al. (Proceedings of the National Academy of Sciences, 2026)
The catecholamines octopamine and tyramine undoubtedly have a major impact on the life of an insect. A wide range of physiological processes and behaviors are regulated by these neurotransmitters/hormones. Octopamine and tyramine act homologous to the adrenergic system of vertebrates, primarily adapting the organism to the given situation, by switching between the states of alertness and rest. Interestingly, higher brain functions like learning and memory are also regulated by octopamine and tyramine. About 30 y ago, initial work in Drosophila demonstrated that dopaminergic neurons signal punishment, while octopaminergic neurons signal reward during olfactory associative learning and memory. In the meantime, however, it has become clear that distinct types of dopaminergic neurons convey both reward and punishment signals to the mushroom bodies, a central brain region responsible for the formation and storage of associative memories. Although some conflicting data remain, these findings challenge the previously established model of functional segregation and may limit the proposed role of octopamine neurons in mediating reinforcing information during memory formation. We have therefore re-examined the role of octopamine in learning and memory in Drosophila larvae. Our findings suggest that optogenetic activation of octopaminergic neurons is sufficient to drive appetitive and aversive memory formation. Further, through a combination of Ca 2+ imaging, anatomical studies, and loss-of-function behavioral approaches, we demonstrate that octopamine signaling plays a crucial role in larval learning by modulating dopaminergic neurons across distinct cell clusters to orchestrate memory processes.